Global Reduction in HIV-related Maternal Mortality: ART as a Key Strategy - Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2015)
Dr. Holtz and colleagues present a synthesis of evidence from published studies over the previous decade on the collective impact of HIV-targeted interventions on maternal mortality. Amongst an assortment of interventions [that include antiretroviral therapy (ART), micronutrients (multivitamins, vitamin A and selenium), and antibiotics], only ART reduced maternal mortality among HIV-infected pregnant and post-partum mothers. These ﬁndings have fundamental and global strategic implications. They are also timely since they provide the evidence that ART reduces HIV-related maternal mortality, and by further enhancing access to ART in HIV-challenged and poor regions of the world, signiﬁcant improvement in maternal morbidity and mortality indices could be attained. The paper bears good tidings and sound scientiﬁc proof that the ﬁnancial investment made globally by government and non-governmental organizations and agencies to reduce the global burden of HIV/AIDS primarily by making ART more accessible to regions of the world most affected by the epidemic is beginning to show beneﬁcial effects not only in terms of numerical reductions in the rates of new cases of HIV/AIDS among women, but also in maternal mortality levels.